2006
DOI: 10.1007/s10457-004-2370-4
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Glomale Mycorrhizal Fungi in Maize/Sesbania Intercrops and Maize Monocrop Systems in Southern Malawi

Abstract: The study investigated diversity and frequency of occurrence of glomale (Arbuscular-or Vesicular Arbuscular-) mycorrhizal fungi on three farming systems in a drought prone and nitrogen deficiency site in southern Malawi. The farming systems comprised of two agroforestry systems of Sesbania sesban (L) Merr intercropped with maize and Sesbania macrantha E Phillips & Hutch. intercropped with maize and a maize monocrop systems without fertilizer, with nitrogen, phosphorus and a combination of nitrogen and phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 17 publications
0
14
0
1
Order By: Relevance
“…Maize monoculture has been estimated to contain up to 5-18 AMF species related with different agricultural practices (Oehl et al, 2004;Bhadalung et al, 2005;Jefwa et al, 2006). Hence, it is difficult to compare results using different methods for estimating AMF diversity.…”
Section: Resultsmentioning
confidence: 99%
“…Maize monoculture has been estimated to contain up to 5-18 AMF species related with different agricultural practices (Oehl et al, 2004;Bhadalung et al, 2005;Jefwa et al, 2006). Hence, it is difficult to compare results using different methods for estimating AMF diversity.…”
Section: Resultsmentioning
confidence: 99%
“…Khanam et al (2006) also found a positive correlation between soil nutrients levels (N, K, OM) and spore numbers in agricultural crops in Bangladesh. Nevertheless, the opposite has been observed in relation to total AMF spore density, which supported the generalisation that inorganic fertilisers may have a deleterious effect on many glomeromycotan species (Jefwa et al 2006). Among soil nutrients, phosphorus is considered to reduce the composition and diversity of AMF communities as well as spore and mycelium densities in both temperate and tropical systems (Agwa and Al-Sodany 2003;Oehl et al 2004;Jansa et al 2005;Khanam et al 2006).…”
Section: Soil Nutrient Availabilitymentioning
confidence: 93%
“…In return, AMF supply nutrients such as phosphorus, nitrogen (N), calcium (Ca), copper (Cu), manganese (Mn), sulphur (S) and zinc (Zn) (Sieverding, 1991;Ortas, 2002). But when the soil is rich in necessary nutrients, plants may not waste more energy for the association with AMF and go for the cheapest source of energy, and individual plant species and plant communities in natural and farming systems affect the distribution and diversity of AMF species (Dalpe et al, 2000;Jefwa et al, 2006). Therefore, according to the previous investigators, AMF spore density, diversity and rates of root colonization are dependent on soil physicochemical properties (Mahmud et al, 1999) and plant species density and richness (Allsopp and Stock, 1992).…”
Section: Introductionmentioning
confidence: 99%